A comparison of anatomical and dosimetric variations in the first 15 fractions, and between fractions 16 and 25, of intensity‐modulated radiotherapy for nasopharyngeal carcinoma*. (4th November 2013) - Yang, Haihua; Tu, Yu; Wang, Wei; Hu, Wei; Ding, Weijun; Yu, Changhui; Zhou, Chao
Abstract : The purpose of this study was to compare anatomical and dosimetric variations in first 15 fractions, and between fractions 16 and 25, during intensity‐modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC). Twenty‐three NPC patients who received IMRT in 33 fractions were enrolled. Each patient had two repeat computed tomography (CT) scans before the 16th and 25th fraction. Hybrid IMRT plans were generated to evaluate the dosimetric changes. There was a significant decrease of the transverse diameter of nasopharyngeal and neck as well as gross tumor volume (GTV) in the primary nasopharyngeal carcinoma (GTVnx) and involved lymph nodes (GTVnd) during the first 15 fractions, and between fraction 16 and 25 ( p < 0.05 ) . Consequently, there was a significant reduction of the percentage of the volume receiving the prescribed dose ( V 100 ) of CTV1 and GTVnd, which was more prominent after the first 15 fractions treatment compared to that between fraction 16 and 25 ( p < 0.05 ) . Additionally, there was a significant increase in the mean dose (Dmean) and percentage of volume receiving ≥ 30 Gy ( V 30 ) to the bilateral parotid in the first 15 fractions ( p < 0.05 ), but not between fraction 16 and 25. While the maximum dose to the spinal cord was significantly increased both in the first 15 fractions, and between fraction 16 and 25 ( p < 0.05 ), the increase of the percent of spinal cord volume receiving ≥ 40 Gy ( V 40 ) was significantly higher in the first 15 fractions compared to that between fraction 16 and 25 ( p < 0.05 ) . Based on the dose constraint criterion in the RTOG0225 protocol, a total 39.1 % ( 9 / 23 ) of phantom plan 1 (generated by applying the beam configurations of the original IMRT treatment plan to the anatomy of the second CT scan) and 17.4 % ( 4 / 23 ) of phantom 2 (generated by applying the beam configurations of the replan 1 to the anatomy of the third CT scan) were out of limit for the dose to the normal critical structures. In conclusion, our data indicated that anatomic changes resulted in more predominant dosimetric effects in the first 15 fractions, and between fractions 16 and 25, of IMRT. PACS number: 87.53.Bn, 87.55.de, 87.55.Qr